Mercury and Selenium in Blood and Epidermis of Bottlenose Dolphins (Tursiops truncatus) from Sarasota Bay, FL: Interaction and Relevance to Life History and Hematologic Parameters - Woshner, Victoria; Knott, Katrina; Wells, Randall; Willetto, Carla; Swor, Rhonda; O’Hara, Todd (EcoHealth, 2008)
Blood and epidermal biopsies from free-ranging Tursiops truncatus captured and released during either summer or winter health assessments in Sarasota Bay, FL, were evaluated for concentrations of mercury, selenium, stable isotopes (δ 13 C and δ 15 N), and blood glutathione peroxidase activity in conjunction with routine hematology and serum chemistry panels. Major objectives were to: 1) quantify and describe relationships among mercury, selenium, glutathione peroxidase, and stable isotopes of C and N in blood and epidermis; 2) elucidate major parameters that influence blood mercury and glutathione peroxidase activity; 3) relate measures of tissue mercury, selenium, and glutathione peroxidase to specific ecological, hematological, morphological, or life history parameters, including season, sex, age, and trophic level. Mercury in both tissues examined is almost exclusively methylmercury. Epidermal concentrations of mercury and selenium reflect their respective amounts in blood, albeit at several times blood concentrations of mercury. The strong association between blood mercury and serum selenium, in conjunction with a lack of significant correlation between blood mercury and glutathione peroxidase, implies that a substantial proportion of blood mercury is affiliated with another selenium-containing moiety or is related to recent dietary intakes (e.g., trophic level, intensive fish consumption). Circulating blood mercury may be described in terms of serum selenium concentration, along with interaction terms among serum selenium, blood δ 15 N, and age. Current selenium concentrations in Sarasota Bay dolphins appear adequate for maintenance of blood glutathione peroxidase activity. However, dolphins evidently are subject to seasonal exacerbation of oxidative stress, which might render them more vulnerable to toxic effects of mercury.